Exploring the acceptability of remote care for people with psychotic disorders in the community: practical challenges and desired features - Abdel-Halim, Nadia; Kuhn, Ronja; Bourdin, Sarah; Healey, Patrick; Bird, Victoria; McNamee, Philip (Frontiers in Psychiatry, 2025)
IntroductionPeople with psychosis are more likely to experience paranoia, which can be worsened by technology use, and have lower digital literacy comparative to the general population and other serious mental illness populations (e.g., recurrent depression). The expedited uptake of remotely delivered mental healthcare by secondary mental health services in the UK in recent years (most notably during the height of the COVID-19 pandemic) provides an opportunity to understand how service users with psychosis, and their clinicians, view the impact of rising digitization within mental health services. This study aimed to explore the present factors encouraging and discouraging the use of remote care options through using the example of a face-to-face intervention, DIALOG+, currently being developed to be delivered remotely. A secondary objective was to identify which requirements need to be met for clinicians and service users to willingly adopt novel remote interventions.Methods9 workshop-focus groups were conducted in total, 6 with service users with psychosis (n= 17) and 3 with clinicians (n=21). Participants were recruited from community mental health services from urban (East London) and rural (Cornwall) settings so that comparisons could be made across contexts. Workshop-focus groups were recorded and transcribed before analysis using the framework method.ResultsThe analysis identified four overarching themes: Factors influencing the acceptability of remote care; Adaptability of remote care for inclusivity; Influence of remote care on therapeutic relationships; and Desirable features in remote care.DiscussionsService users and clinicians did not view remote delivery of care as a completely adequate substitute for in-person care but were receptive to its integration into hybrid models when both patient choice and clinician judgment were respected. The study highlights the need for software design to address resource limitations and individual differences, while considering the influence of training, device availability, and urbanization on remote care implementation.